Image Retrieval of Earth-like Planets from Light Curves. Issue Volume 8:Issue S293(2012) (29th April 2014) - Kawahara, Hajime; Fujii, Yuka
Abstract: Surface environment of habitable exoplanets will be important for astrobiologists on exoplanets in near future. Diverse surface environments on the Earth including continents, ocean, and meteorological condition (clouds and rains) serve as the backbone of biodiversity. One of the promising approaches to know the landscape of the terrestrial exoplanets is to use scattered light of the planet through direct imaging. Since spin rotation and orbital revolution change illuminating area on planetary surface and cause time variation to disk-integrated brightness, light curves carry spatial information on the planetary surface. We propose an inversion technique of annual reflected light curves to sketch a two-dimensional albedo map of exoplanets, named the spin-orbit tomography (SOT). Applying the SOT to realistic simulations of the reflected light of an Earth-twin, we demonstrate how the SOT works. The mean cloud and continental distributions can be roughly obtained with single band photometry and difference of two-bands photometry, respectively. The SOT retrieves the planetary image without actually resolving the planet, which can be used to know the habitat of the exoplanets in near future.